Implementation of closed-loop field-oriented control for PMSM on rehabilitation robot using BTS 7960 - Nathalia, Vita Ayu; Adiputra, Dimas; Putranto, Rifki Dwi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
The efficiency of control systems in permanent magnet synchronous motors (PMSM) is crucial, especially for applications in physiotherapy robots. Previous studies have demonstrated that an open-loop field-oriented control (FOC) driver using BTS7960 outperforms the commonly used electronic speed controller (ESC). This research addresses the challenge of further improving efficiency by employing a closed-loop FOC driver with the BTS7960. The research methodology involves two main stages. First, a PSIM software simulation of a closed-loop FOC using a proportional integral (PI) controller is conducted. The aim is to determine the P and I parameters that result in the smallest settling time, steady-state error, and overshoot in controlling the PMSM motor's rotation per minute (RPM). The second stage involves hardware implementation with the BTS7960, where the PMSM motor RPM is compared under various loads ranging from 10-gram to 60 gram. RPM results from both open-loop and closed-loop configurations are compared. The results show that the closed-loop FOC driver has improved system transient response compared to the previous open-loop FOC driver, notably reducing the settling time from 2.24 seconds to 1.45 seconds for a 60 gram load. Therefore, this research concludes that a closed-loop configuration with well-tuned PI parameters can deliver better performance compared to open-loop methods, as clearly demonstrated.